Aplikasi Animasi Pada Materi Tata Surya Sekolah Dasar Berbasis Android - Ifah, Muzdalifah (AhInstitute of Research and Community Service (LP2M) Institute of Social Sciences and Business Andi Sapada, 2023)
He design of the Learning Animation application with the multimedia method in Elementary Schools is carried out by making learning games about the solar system aiming to facilitate and support learning activities, especially learning science. The role of animation in learning to attract students' attention and strengthen motivation to learn. This animation is in the form of moving text or pictures, funny animations that can attract students' attention. The resulting design consists of 4 Scenes, namely the Material Menu Scene, Quiz Game Scene, Profile Scene and Exit Scene from the application, based on the trial results has been running well and can be downloaded on the default android application and makes learning fun so that it can increase student learning motivation.